An improved damping adaptive grid‐forming control for black start of permanent magnet synchronous generator wind turbines supported with battery energy storage system. Issue 2 (6th January 2023) - Meng, Jianhui; Wang, Dongxu; Wang, Yi; Guo, Feng; Yu, Jie
Abstract: Permanent magnet synchronous generators (PMSGs) equipped with back‐to‐back grid‐forming converters have the ability to form a 100% renewable energy power grid. Black‐start is the key capability of grid‐forming converters when restoring the system from a blackout. It is necessary for a grid‐forming converter of the PMSG to operate in black‐start and grid‐connected active support modes. This paper investigates an improved damping adaptive grid‐forming (DA‐GFM) control method for PMSG wind turbines to suppress system frequency fluctuations and achieve a smooth black start. The proposed DA‐GFM control introduces the frequency variations and natural constant function to adaptively adjust its damping coefficient in the dynamic operating progress. The implementations and effects of the proposed DA‐GFM control method on the grid‐forming converter are theoretically evaluated. Additionally, the detailed black‐start operation process is completely studied through a microgrid system with two PMSG wind turbines and energy storages. Compared with the conventional grid‐forming control, the proposed control scheme can not only suppress frequency fluctuations better, but also achieve a smooth forming power grid process. Finally, experiment tests on a controller‐level hardware‐in‐the‐loop simulation platform are carried out to validate the proposed control strategy for achieving a smooth black start. Abstract : This paper investigates an improved damping adaptive grid‐forming (DA‐GFM) control method for PMSG wind turbines to suppress system frequency fluctuations and achieve a smooth black start. Additionally, the detailed black‐start operation process is completely studied through a microgrid system with two PMSG wind turbines and energy storages.